1998
DOI: 10.1021/jp980252a
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hole Burning and Solvation Dynamics of Chlorophyll b Monomers in Various Solvent Environments

Abstract: We present a femtosecond transient absorption study of chlorophyll b monomers in various solvent environments. Transient absorption spectra and kinetics of chlorophyll b were measured in neat pyridine and acetone. The kinetics were measured also for three samples of chlorophyll b dissolved in 3-methylpentane and titrated with pyridine. Characteristic for all chlorophyll b samples is a very strong excited-state absorption, which significantly affects time-resolved anisotropy values in the wavelength region of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The results provide direct information as to which wavelengths are best for monitoring energy transfer and at which wavelengths the transient absorption signal, and concomitantly the transient absorption anisotropy, are strongly influenced by excited state absorption. Similar information has previously been reported for chlorophyll a [18] and chlorophyll b [19] in pyridine.…”
Section: Introductionsupporting
confidence: 89%
“…The results provide direct information as to which wavelengths are best for monitoring energy transfer and at which wavelengths the transient absorption signal, and concomitantly the transient absorption anisotropy, are strongly influenced by excited state absorption. Similar information has previously been reported for chlorophyll a [18] and chlorophyll b [19] in pyridine.…”
Section: Introductionsupporting
confidence: 89%
“…Early time DAS spectra at 490 nm excitation (Fig. 6Sa in ESM) show positive amplitudes (rise of ESA) around 652 nm most (Oksanen et al 1998;Martinsson et al 1999). Around 680 nm positive amplitudes (rise of Chl a bleach/stimulated emission, SE) appear at early times but turn into negative amplitudes at later times (decay of Chl a bleach/SE).…”
Section: Nm Excitationmentioning
confidence: 96%
“…It was found that the sensitivity of the Q y band to hydrogen bond donors is larger than that of the Q x band. [106,118] The oscillator strengths of chlorophyll pigments also depend on the solvent. For example, for Chl a a range of the extinction coefficient from 6.14 10 À4 mol À1 cm À1 in cyclohexane to 8.52…”
mentioning
confidence: 99%
“…[119,120] Depending on the scheme, there are quite large differences in the extrapolated vacuum value. [120] Other possible solvent effects which might influence the absorption spectra of chlorophylls are self-aggregate breaking [118] or aggregate formation induced by the solvent molecules (see ref. [93] and references therein).…”
mentioning
confidence: 99%